Anthocyanins from Purple Tomatoes as Novel Antioxidants to Promote Human Health - Silvia Gonzali; Pierdomenico Perata (MDPI AG, 2020)
Anthocyanins are plant secondary metabolites belonging to the class of polyphenols, whose beneficial roles in the prevention and treatment of several important human diseases have been demonstrated in many epidemiological studies. Their intake through diet strictly depends on the eating habits, as anthocyanins are contained in red and purple fruit and vegetables as well as in some processed foods and beverages, such as red wine. Genetic engineering and breeding programs have been recently carried out to increase the content of anthocyanins in candidate plant species which cannot offer satisfactory levels of these precious compounds. Tomato (Solanum lycopersicum) is a vegetable commodity where these strategies have resulted in success, leading to the production of new anthocyanin-rich fruit varieties, some of which are already marketed. These varieties produce purple fruits with a high nutraceutical value, combining the health benefits of the anthocyanins to the other classical tomato phytochemicals, particularly carotenoids. The antioxidant capacity in tomato purple fruits is higher than in non-anthocyanin tomatoes and their healthy role has already been demonstrated in both in vitro and in vivo studies. Recent evidence has indicated a particular capacity of tomato fruit anthocyanins to act as scavengers of harmful reactive chemical species and inhibitors of proliferating cancer cells, as well as anti-inflammatory molecules.